“Reaction of the USD/PLN Exchange Rate to Published Macroeconomic Data under Conditions of Imperfect Information: Data Analysis from October 2018 to December 2023” - Jolanta PASIONEK (Communications of International Proceedings, 2025)
The foreign exchange market is the largest and most dynamic financial market globally, with exchange rates predominantly influenced by economic factors. U.S. macroeconomic data play a critical role in driving short-term volatility in exchange rates. This study examines the impact of U.S. macroeconomic data releases on short-term volatility in the USD/PLN exchange rate under conditions of imperfect information. The aim is to identify which macroeconomic indicators most significantly affect fluctuations in this currency pair. This research addresses a significant gap in the existing literature, as no prior studies have specifically investigated the effect of six types of U.S. macroeconomic data on the USD/PLN exchange rate within the M30 interval. The findings are intended to provide valuable insights for Forex market participants trading the USD/PLN pair, helping them make more informed investment decisions. The study employs regression and statistical analysis techniques, utilizing a linear regression model with a GARCH process to model the stochastic component. Parameters were estimated using 30-minute exchange rate data for three currency pairs, with the analysis conducted in Stata 15. The results demonstrate that USD/PLN volatility increases following the release of U.S. macroeconomic data. The most notable reactions were observed after the release of Non-Farm Employment Change and Consumer Price Index data, while New Home Sales and Unemployment Claims also triggered significant responses. The COVID-19 pandemic was linked to elevated volatility in the USD/PLN exchange rate, while the outbreak of the war in Ukraine further intensified fluctuations in this currency pair.
Keywords: Foreign Exchange Markets; currency exchange rates; GARCH model.